Development of An Animated Video on the Digestive System That Promotes Healthy Eating Habits to Enhance Elementary School Student’s Understanding - Multazama Multazama; Rita Istana; Annisa Nurramadhani (Journal of Educational Sciences, 2026)
This study aimed to develop an animated video about the human digestive system integrated with healthy eating education to improve elementary school students’ conceptual understanding and awareness of healthy eating habits. The study employed a Research and Development (R&D) method using the ADDIE model consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The research involved 26 fifth-grade students at SDN Tegallega 2 Bogor. The product was a 6–7 minutes animated video developed using Canva, combining narration, illustrations, animation, and audiovisual elements to explain digestive processes while promoting balanced nutrition and healthy eating habits. Data were collected through observations, interviews, questionnaires, and pretest–posttest assessments and analyzed using descriptive qualitative, percentage, and N-Gain analyses. Media, language, and material expert validations obtained 91%, 100%, and 92%, respectively, while teacher and student responses reached 89% and 90%. The average score increased from 65 to 92 with an N-Gain of 0.79 (high). Student responses indicated better understanding of healthy food choices after using the media. These findings indicate that the animated video effectively improved conceptual understanding while supporting healthy eating awareness.